2020
DOI: 10.1038/s41598-020-59458-6
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness and physical activity association with cognitive function and quality of life: baseline cross-sectional analysis of the PREDIMED-Plus trial

Abstract: Physical activity (PA) has been hypothesized to be effective to maintaining cognitive function and delay cognitive decline in the elderly, but physical fitness (PF) could be a better predictor of cognitive function. We aimed to study the association between PA and PF with cognitive function and quality of life using cross-sectional data from 6874 participants of the PREDIMED-Plus trial (64.9 ± 4.9 years, 48.5% female). PF and PA were measured with a Chair Stand Test, the REGICOR and Rapid Assessment Physical A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 54 publications
2
50
0
3
Order By: Relevance
“…Studies by Whiteman et al [34] and Khan et al [35] have recognized that high levels of physical activity promoted brain changes that can be explained by increased oxygenation and tissue irrigation, as well as increased metabolic activity, providing improved neurological development. Thus, the role of the intensity of the physical activity could also be a determining factor [36]. Similarly, other studies have indicated significantly improved brain function and behavioral performance after physical activity interventions [37,38].…”
Section: Discussionmentioning
confidence: 91%
“…Studies by Whiteman et al [34] and Khan et al [35] have recognized that high levels of physical activity promoted brain changes that can be explained by increased oxygenation and tissue irrigation, as well as increased metabolic activity, providing improved neurological development. Thus, the role of the intensity of the physical activity could also be a determining factor [36]. Similarly, other studies have indicated significantly improved brain function and behavioral performance after physical activity interventions [37,38].…”
Section: Discussionmentioning
confidence: 91%
“…These combined interventions, energy-restricted MD with higher intake of polyphenols and physical activity, were significantly associated with an improvement of compounds of metabolic syndrome among subjects involved such as inflammatory biomarkers and blood cholesterol and triglycerides [ 12 - 15 ]. This large trial has also demonstrated that MD may improve the general quality of life of subjects and physical activity may have benefits on quality of life and cognitive functioning [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization's (WHO) definition, we can associate HRQoL with the impact a disease has on our perception of happiness, position in life and on our physical, psychological, social and spiritual well-being [18]. Evidence suggests that doing 150 to 300 min of moderate PA per week and following the Mediterranean diet provide considerable benefits in maintaining health, healing and in HRQoL [17,[19][20][21][22][23][24]. Overweight/obesity are the main determinants of metabolic syndrome (MetS) and there are increasing numbers of studies that use HRQoL in individuals with MetS, since it is considered a strong predictor of disability and long-term mortality [25][26][27].…”
Section: Introductionmentioning
confidence: 99%